If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(3x+2)-5(6x-1)=2(x-8)-5(7x-6)+8
We move all terms to the left:
6(3x+2)-5(6x-1)-(2(x-8)-5(7x-6)+8)=0
We multiply parentheses
18x-30x-(2(x-8)-5(7x-6)+8)+12+5=0
We calculate terms in parentheses: -(2(x-8)-5(7x-6)+8), so:We add all the numbers together, and all the variables
2(x-8)-5(7x-6)+8
We multiply parentheses
2x-35x-16+30+8
We add all the numbers together, and all the variables
-33x+22
Back to the equation:
-(-33x+22)
-12x-(-33x+22)+17=0
We get rid of parentheses
-12x+33x-22+17=0
We add all the numbers together, and all the variables
21x-5=0
We move all terms containing x to the left, all other terms to the right
21x=5
x=5/21
x=5/21
| (2x-10)-24=5x-(-6+8x) | | 4(x-1)-(2x-5)=5 | | 4(x-1)-(2x-5)=8 | | -d=1 | | 7+4x=49 | | 11=6c | | -5m+(-7)=-25 | | (n-2)180/n=900 | | (5x)+(4x-9)=180 | | X=3.5-y | | 7x+3-1=56-2 | | 3200(.045)(8)=x | | 4x(2x-4)=7x(1x+5) | | 4x+9=99−6x | | 10*x=17 | | 1500(.04)(3)=x | | 1500(.4)(3)=x | | 0.60x+0.45(20)=0.30(60) | | 1/4b+10=24 | | 7/2x-5/3x=11 | | -13m=13 | | 90x+52=90 | | 180x+52=180 | | 11/3n-5/9=5/6 | | 5x=2/4 | | 28=26+9t-4.9t^2 | | -13c=26 | | p^2+2p+9=0 | | 13m-7=71 | | 4s+26=86 | | 15x-3(2x-4)=8x+7 | | 75/x+3=84 |